Peningkatan Keterampilan Dasar Menari Melalui Pembelajaran Berbasis Gamifikasi Pada Mata Pelajaran Pendidikan Lingkungan Budaya Jakarta Kelas IV-A SDN Jatinegara 15 Pagi - Handayani, Tiara Putri (Program Studi Pendidikan Tari FBS UNJ, 2025)
This study aims to improve basic dancing skills through gamification-based learning in Jakarta Cultural Environmental Education learning for IV-A students of SDN Jatinegara 15 Pagi with a total of 30 students. The research method used is Classroom Action Research which adapts the Kemmis & McTaggart model and is carried out in two cycles where each cycle consists of four stages, namely planning, implementation, observation, reflection. The results of the study showed that there was an increase in basic dancing skills after the application of gamification-based learning in the Jakarta Environmental and Cultural Education (PLBJ) content which was marked by an increase in students' dancing skills in each cycle. The basic dancing skills of students in cycle I reached a percentage of 70%. In cycle II it increased to 83%. Thus it can be concluded that if the application of gamification-based learning is applied, it can improve students' basic dancing skills.